Estudo experimental e de simulação da fluidodinâmica e recobrimento em leito de jorro - Duarte, Claudio Roberto (2006)
The spouted bed technique has found application in many industrial processes such as drying of granular materials, blending of polymer chips, coating of tablets, and granulation of fertilizers and other materials. Although has an extensive application, the mechanisms of solids movement in spouted beds are still not completely understood. The knowledge of the solids flow pattern in spouted beds is of great interest in their design because the particle trajectories must meet the requirements of the process being carried out. The literature shows several studies on the fluid-dynamic of the spouted bed, however in general, the works present restricted models to specific regions of the bed and limited to operational conditions. There are a restrict number of works related to the fluid dynamic study of the spouted bed using a model Eulerian Multiphase. In this work, the Eulerian multiphase model, which treats gas and particle as interpenetrating continuum was used to different spouted bed configurations.The characteristic fluid-dynamic profiles of the spouted bed was obtained in this work. The technique of computational fluid-dynamic was used and the granular Eulerian model was adopted. The fluid-dynamic profiles of the particle and fluid, for different configurations of the bed were simulated and validated with experimental data. In this work the particle velocity, minimum spouting flow rate and characteristic fluid-dynamic curves of the spouted bed obtained with simulations shows a good agreement with experimental data. The spouted bed with a draft tube was simulated with different configurations and was possible identified the adequate configurations to recovering soybean seed. The covering of soybean seeds with bacteria and micronutrients enhances vigorous growth of the plant thereby avoiding use of ammoniacal fertilizers. In the spouted bed covering can be done by pulverization of the coater slurry on the soybean seeds using a pneumatic atomizer. In this work, was compared the coating heterogeneity of particle recovering in spouted bed and others equipaments useds in the farm. The heterogeneity was measured with the dispersion indice and the spouted bed shows a coating more homogeneous than other equipments studied. The optimum thickness of the cover allows the fundamental gaseous interchanges for germination and provides the ideal conditions for bacterium activity. A simulation of the mass distribution of seeds was obtained using a population balance model. The validation of population balance model was obtained using ten experiments of coating of soybean seeds in spouted bed.